Sejarah Nabi Muhamad Saw Pada Piagam Madinah - Nugraha, Acep (JURNAL KAJIAN ISLAM MODERN, 2023)
Referring to the Medina Charter, it explicitly states the names of several groups and several tribes. It seems that the Prophet really knew about the conditions and politics of each of these groups. The Prophet Muhammad SAW was able to establish himself as the leader of Medina in the midst of various tribes who believed in him as the leader of society. Islam was implanted by him as a unity of Religion and Politics. The Prophet succeeded in creating one nation under one leadership, an embodiment of the great idea in the form of the principles of Arabian national life, and he was able to make Islam a religion that produces reconciliation.